Reproductive disruption in Fasciola hepatica associated with incomplete efficacy of a new experimental formulation of triclabendazole - Scarcella, Silvana Andrea (2011)
The objective of the present study was to analyse the reproductive viability (using histopathologic studies) of Fasciola hepatica from cattle artificially infected and treated subcutaneously with a new experimental formulation of triclabendazole (8 mg/kg b.w.). The results of the efficacy controlled test, which only takes into account the presence of live adult flukes, indicated that, whilst in the control group (n = 7) 533 live specimens were recovered, in the test groups (doses of 8 and 12 mg/kg b.w.) only 195 and 47 adults were recovered, respectively. These numbers indicate efficacies of 69% and 95.6%, respectively. It was observed in that dose of 8 mg/kg b.w. some specimens remained viable, but they were infertile, which severely compromises the biological cycle of the trematode. In the testis tubules of flukes treated with the low dose of TCBZ (8 mg/kg), very few cells were present and the vitelline follicles were markedly reduced in size and each follicle contained very few cells. This would have direct implications for the pathogenesis of the parasitosis since the remaining parasites would produce little clinical–productive manifestations, would stimulate the immune response and would find it difficult to establish future reinfestations/re-infections. Consequently, these observations will also prompt a review of certain methodological and interpretative aspects related to efficacy tests, where the only discriminative factor is the reduction of the adult parasite load. On one hand, histopathological studies could be complementary to the efficacy controlled test for TCBZ or other BZD formulations.